Synthesis, structure, and reactivity of nitrosyl pincer-type rhodium complexes - Gaviglio, Carina del Valle (2009)
Pincer-type linear nitrosyl Rh(I) complexes, Rh(PCPBu)(NO)][BF4] (2) and [Rh(PCPBuCH2)(NO)][BF,4] (8), are reported (PCPBu = 1,3-bis[(di-fer/-butylphosphino)methyl]-2,4,6-trimethylbenzene). Complex 2 was synthesized by reaction of the Rh(I) dinitrogen complex Rh(PCPBu)N 2 (1) with NOBF2, while treatment of the methyl chloride complex Rh(PCPBu)(CH3)Cl (7) with NOBF4 led to the formation of 8. Upon addition of CO, a linear bent nitrosyl equilibrium was established, both in solution and in the solid state, between the linear nitrosyl Rh(I) complex 2 and the bent nitrosyl Rh(III) complex [Rh(PCP'Bu)(NO)(CO)][BF4] (3). Addition of LiCl to complex 2 resulted in the quantitative formation of the bent nitrosyl complex Rh(PCPBu)(NO)(Cl) (4). An IR study of solvent interactions of the nitrosyl ligand of complex 2 in various solvents is also presented, showing a linear bent nitrosyl equilibrium induced by solvent coordination. Treatment of 4 with HBF4 · O(C2H5)2 led to chloride abstraction, with formation of complex 2. Upon addition of NOBF4 to the PNP Rh(I) complex [C5HN(CH2P- (tBu)2) 2Rh(CH3CN)]BF4 (5), the bent nitrosyl complex C5H3N(CH2P(tBu)2) 2Rh(CH3CN)(NO)][BF4]2 (6) was obtained. Employing 15NO-labeled complexes it is possible to assign the bent or linear modes of bonding of NO on the basis of 15N NMR spectroscopy. X-ray structures of all nitrosyl complexes reported here confirm that the tetracoordinate species are square-planar with a linear nitrosyl ligand occupying the position trans to the aromatic ring and the metal is Rh(I), whereas the pentacoordinate complexes adopt a square-pyramidal geometry with a bent apical nitrosyl coordinated to Rh(III).